Bird Diversity, Density and Foraging Activities in a University Campus Landscape in Sarawak - Voon, Audrey Mei Fang; Ku Nasradhi, Ku Nor Azlina; Rahman, Mustafa Abdul; Mohd-Azlan, Jayasilan (Borneo Journal of Resource Science and Technology, 2016)
A total of 77 species from 34 families was recorded from 11,863 observations from November 2012 to April 2013 (six months) within Universiti Malaysia Sarawak (UNIMAS) campus using line transect method. This bird list is dominated by Asian Glossy Starling (Aplonis panayensis) with 4,917 observations (41.45%) followed by Eurasian Tree Sparrow (Passer montanus) with 867 observations (7.31%) and Yellow-vented Bulbul (Pycnonotus goiavier) with 752 observations (6.34%). This study reports higher diversity (H’ = 2.5) compared to previous studies. Density of bird was estimated at 6.24 individuals/ha. In order to explore the interspecific interactions between species, 19 bird species with (1,189 observations) most observations were subjected to bipartite network analysis. Based on the network analysis it appears that birds partition food resources spatially and by food type. The highest niche overlap occurs between foraging technique (0.61) while lower overlap was observed for height (0.44), types of food (0.42) and foraging substrate (0.42). This suggests that birds were exploiting similar resources but segregated spatially. Therefore birds are partitioning their niche to allow coexistence and to adapt to human modified landscape. This study has provided valuable information in characterising the assemblage and understanding the distribution of the birds in a campus landscape.